Comparison of antifungal effects of an experimental fluconazole mouthwash and nystatine mouthwash: An in vitro study - Nader Navabi; Ehsan Momeni; Amin Ayatollahi; Payam Khazaeli; Abbas Pardakhti (Isfahan University of Medical Sciences, 2013)
AbstractIntroduction: Treatment of oral candidiasis with mouthwashes has several advantages. The aim of the present study was to evaluate the clinical efficacy of a new fluconazole suspension on the Candida albicans and compare its effects with those of nystatin.Materials and Methods: In the present in vitro study 10-mg/mL fluconazole mouthwash was formulated in an aqueous suspension. Brookfield viscometer was used to determine particle size and shape for the suspension formulation prepared and the dissolution process of foreign suspension was evaluated. Nystatin suspension (100,000 U/mL) available on the market was used in this study. PTCC5027 standard strains of Candida albicans were provided by the Iranian Collection Center for Infectious Bacteria and Fungi. Clinical samples of Candida albicans were exposed to fluconazole and nystatin suspensions by flow cytometry and macrodilution methods. Experimental results were recorded and analyzed by descriptive-observational method. MICs for both fluconazole and nystatin suspensions were measured.Results: The results showed that 10-mg/mL nystatin and fluconazole suspensions are able to eliminate Candida albicans. MICs for fluconazole and nystatin suspensions were and respectively.Conclusion: Both fluconazole and nystatin suspensions were able to eliminate Candida albicans at a concentration of 10-mg/mL but the results of MIC showed that nystatin had a more potent effect at lower concentrations compared to fluconazole and fluconazole had no particular superiority over nystatin in this respect. Key words: Candida albicans, Fluconazole, Nystatin, Suspensions